Implementation of the Clean Water Sanitation Program in Padangsidimpuan City - Zahwa Naflah Miranda (UM.Tapanuli Selatan, 2026)
Water is a necessary component of human life, therefore, efforts are needed to maintain its quality to ensure its safety. In the health sector, water is an environmental medium that plays a crucial role in disease transmission, as it can serve as a breeding ground for germs and disease. The key to sanitation development lies in socio-cultural factors and community behavior. Poor sanitation conditions can lead to the emergence of diseases and a decline in environmental health. Therefore, a comprehensive sanitation awareness movement is needed within the community. In this study, the author used qualitative research methods and analyzed the data obtained and the results of fieldwork using interview techniques . The results showed that The implementation of the clean water sanitation program carried out by the Padangmatinggi Health Center, South Padangsidimpuan District , is running in accordance with the guidelines of the Ministry of Health of the Republic of Indonesia regarding the Implementation of Drinking Water Quality Surveillance and Basic Sanitation Activities by socializing it to the community, then taking samples to represent the condition of the water supply system and testing it in the laboratory by the Health Service to see whether the water quality is suitable for public consumption or not.